Pendampingan Pembuatan Media Pembelajaran Sparkol Videoscribe Berintegrasi Nilai Islam pada Guru MI Miftahul Ulum Tulung Jaya Lampung Timur - Santi Widyawati; Binti Khoiriyah; Dwilita Astuti; Ummi Rosyidah; Siti Qomariyah; Gunawan Gunawan (Smart Society, 2021)
Informatics and technology are widespread in everyday life. So we cannot avoid using technology. In the world of education, the use of informatics and technology has not been fully utilized. This happens because of the lack of teacher ability in operating the technology. This has inspired us to carry out teacher mentoring activities in making learning media (sparkol videoscribe). This assistance uses the Participatory Action Research (PAR). The purpose of this community service is to assist the creation of sparkol videoscribe learning media that integrates Islamic values for MI Miftahul Ulum teachers, Tulung Jaya, East Lampung. The research subject is the teacher at the school. The results of the study showed that in three cycles all members of the workshop understood well the material presented by the teacher. It is proven that in general their understanding reaches 81%.